Are Karachi Stock Exchange Firms Investment Promoting? - Evidence of Efficient Market Hypothesis Using Panel Cointegration - Arshed, Noman; Hassan, Muhammad Shahid; Grant, Kenneth A; Aziz, Osama (Asian Development Policy Review, 2019)
This study investigates the evidence of efficient market hypothesis for the firms listed in Karachi Stock Exchange (KSE), which signifies the nature of the stock market. According to this hypothesis, the empirical information available is not enough to predict the present movement of share prices. After using the Panel cointegration approach between current share price and past share price in the light unknown structural break on the daily data of 75 selected firms over the period June 2004 to March 2014, comprising 2370 observations per firm. The study found that the firms listed in Karachi Stock Exchange are inefficient firms, therefore, for the case of KSE – 100 offer information which can be used to make economic profits. Hence Karachi Stock Exchange provide enough predictable information using past trends so that investor can gain economic profit from it, so it will take time for the market to become mature and the creation of competition.